Political Economy of Distortions to Agricultural Incentives : Introduction and Summary - Anderson, Kym (World Bank, Washington, DC, 2017)
During the 1960s and 1970s most developing countries imposed anti-agricultural policies, while many high-income countries restricted agricultural imports and subsidized their farmers. Both sets of policies inhibited economic growth and poverty alleviation in developing countries, while doing little to assist small farmers in high-income countries. Since the 1980s, however, many developing countries began to reduce the anti-agricultural bias of sectoral policies, and from the early 1990s the European Union began to move away from price supports to more-direct forms of farm income payments. This paper summarizes a forthcoming book that seeks to explain this evolving pattern of distortions to incentives conceptually and econometrically by making use of new political economy theory and a new globally comprehensive and consistent set of estimates of the changing extent of annual distortions over the past half-century. The distortion estimates involve more than 70 products that cover around 70 percent of the value of agricultural output in each of 75 countries that together account for over 90 percent of the global economy, and they expose the contribution of the various policy instruments (both farm and non-farm) to the net distortion to farmer incentives. Such a widespread coverage of countries, products, years and policy instruments has allowed this collection of studies to test a wide range of hypotheses suggested by the new political economy literature, including the importance of institutions. As a set it sheds much new light on the underlying forces that have affected incentives facing farmers in the course of national and global economic and political development, and hence on how those distortions might change in the future - or be changed by concerted actions to offset political pressures from traditionally powerful vested interests.